New research on the terramare of northern Italy - Pearce, Mark
The north Italian Bronze Age cultureÐthe terramareÐhas recently been celebrated in a splendid exhibition at Modena, and new catalogues, research and the re-opening of old excavations. Mark Pearce discusses the relevance of the old ideas in the light of new data.